Synthesis of Ultrafine WC-Co Core-shell Composite Powders by Chemical Reduction Method - Zhang, Xinghe; Liao, Li; Wang, Yujie; Ye, Jinwen; Xie, Kenan (Asian Journal of Chemistry, 2011)
The WC-Co core-shell composite powders were prepared by a solution chemical reduction method. The resulting ultrafine composite powders were investigated by X-ray diffraction, scanning electron microscopy and energy dispersive spectroscopy, respectively. The core-shell microstructure (tungsten carbide coated with cobalt shell) was confirmed by the characterization results. It reveals that the present chemical reduction method is an effective route to synthesize ultrafine WC-Co core-shell composites, which would be benefit to inhibit the discontinuous grain growth and binder pooling during the sintering cemented carbide.